Predominant Challenges of COVID-19 to Students’ Personal Learning Endeavors: Illustrative Case Study in a Philippine University - Toquero, Cathy Mae Dabi; Ulanday, Diane Mae P.; Pantao, Jovar G.; Pelones, Maria Theresa P. (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Background: The COVID-19 pandemic created psychological chaos, social distress, and emotional disturbances to the students worldwide which affected their pursuit to focus on their learning goals. This article examines the psychosocial, educational, and other related challenges of the current crisis which threaten the space for learning heuristics and personal well-being of university students. Methods: The study applied an illustrative case study design to describe the real-life situations of the students in from a state university in the Philippines during the early stages of a phenomenal health event in history. Results: Result indicates that COVID-19 posits detrimental effects to the students’ educational cycles and psycho-social well-being as they felt drowned, trapped, and annihilated at the arrival of COVID-19. Aside from the psychological dilemma, students also deal with emotional, virtual, social, technical, and educational-related challenges. Conclusions: The educational momentum of these particular students declined due to unprecedented educational transitions, decreased motivation for their studies, complexities experienced in the emergency online learning environments, and multiplex health and digital issues.